قراءة معاصرة في فقه الاختلاف كحقيقة دينية وضرورة شرعية وحاجة بشرية - Salah Mohamed Zaki 'Ibrahim Al-Qadiri (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceedings Of The International Conference On Da’wah And Islamic Management (IC-DAIM 2021) “Humane Leadership and Da’wah For Sustainable Future of Ummah” 26-27 October 2021 Organized by: Da’wah and Islamic Management Program, Faculty of Leadership and Management, USIM